The Autonomous Image : Cinematic Narration and Humanism - Prats, A. J., 1948- (Book collections on Project MUSE., 1981)
Blowup, says Armando Prats, is one of the necessary movies. It is a ""living expression of the transition into the new narrative domains"" in terms of man's ""new vision of himself as a narrative creature in a world whose very essense is cinematic narration."" Prats' work on the new humanism inherent in postwar filmmaking is a rewarding work with implications for the fields of esthetics and axiology as well as film criticism. In his analyses of four films by three directors -- Fellini's Director's Notebook and The Clowns, Wertmiller's Seven Beauties, Antonioni's Blowup -- Prats shows the